A new synonym of Bathseba Motschulsky, 1866 (Chrysomelidae, Eumolpinae, Typophorini) with a new species and redescription of B. bifasciata (Jacoby, 1895) n. comb. and other taxonomic and biological notes - Kumari, Amritha; Moseyko, S. A. G.; Prathapan, K. D. (Zootaxa, 2023)
Tricliona Lefèvre, 1885 n. syn. is a new junior synonym of Bathseba Motschulsky, 1866. Bathseba syzygium n. sp., a pest of Syzygium cumini (L.) Skeels (Myrtaceae) in south India, is described and illustrated. Bathseba bifasciata (Jacoby, 1895) n. comb. is redescribed and illustrated. Bathseba bengalensis (Jacoby, 1908) n. syn. is synonymized with B. indica (Jacoby, 1900). Cleoporus variegatus Jacoby, 1904 is transferred to Bathseba and Tricliona subdepressa Jacoby, 1908 n. syn. is treated as its synonym. Tricliona foveipennis Bryant, 1950 is transferred to Gressittella Medvedev, 2009. Mangifera indica L. and Anacardium occidentale L. (both Anacardiaceae) are reported as host plants of B. bifasciata for the first time.